2019
DOI: 10.1088/1361-6463/ab08c1
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive and selective surface plasmon resonance sensor employing a gold-supported graphene composite film/D-shaped fiber for dopamine detection

Abstract: An Au film/graphene D-shaped plastic optical fiber (D-POF) functionalized with dopaminebinding aptamer (DBA) was proposed to achieve a sensitive and specific detection of the small molecule dopamine. The surface plasmon resonance sensor combines the virtues of a D-shaped fiber, the transfer of graphene via gold film, and the amplification of the refractive index with the conformational transformation of DBA. The sensitivity of the Au film/graphene D-POF sensor (1539 nm/RIU) is higher than that without graphene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…N. Cennamo et al investigated the effects of different photoresist buffer layers on the POF-based SPR sensor performance [ 25 ], and a POF-SPR-based magnetic field sensor [ 26 ] and a fluorescent POF-based SPR sensor [ 27 ] were also proposed by the same group. In addition, a gold-supported graphene composite film-coated POF-based SPR sensor for dopamine detection was also reported [ 28 ]. The recent developments of the POFs-based SPR sensors have demonstrated that they are playing a more and more important role in the SPR sensing fields.…”
Section: Introductionmentioning
confidence: 99%
“…N. Cennamo et al investigated the effects of different photoresist buffer layers on the POF-based SPR sensor performance [ 25 ], and a POF-SPR-based magnetic field sensor [ 26 ] and a fluorescent POF-based SPR sensor [ 27 ] were also proposed by the same group. In addition, a gold-supported graphene composite film-coated POF-based SPR sensor for dopamine detection was also reported [ 28 ]. The recent developments of the POFs-based SPR sensors have demonstrated that they are playing a more and more important role in the SPR sensing fields.…”
Section: Introductionmentioning
confidence: 99%
“…In extrinsic fiber sensors, optical fibers are used only to connect a sensing region with a light source and a detector. Up to now, intrinsic and extrinsic fiber-optic SPR sensors have been realized for sensing in environmental, security, industrial, biomedical, and biochemical sectors, detecting from small chemical compounds to more complex biological molecules such as proteins [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that graphene enhanced the sensitivity and played a role in amplification of the SPR signal by introducing DBA. They demonstrated the potential of this sensor to detect DA-induced disorders [ 136 ]. Graphene improved the sensor sensitivity and amplified the SPR signal.…”
Section: Da Detection Using Spr Biosensorsmentioning
confidence: 99%